Methanolic pomegranate dried peel extract improves cryopreserved semen quality and antioxidant capacity of rams - Amal M Aboelmaaty; Mohamed S Kotp; Aya M Fadl; Elshymaa A Abdelnaby; Islam E El-Seadawy; Hossam R El-Sherbiny (Asian Pacific Journal of Reproduction, 2023)
Objective: To select the appropriate concentrations of methanolic pomegranate extract supplemented in rams' semen extender for obtaining the best-cryopreserved semen quality. Methods: Tris-based semen extender was supplemented with 0.0, 0.40, 0.48, and 0.56 mg/mL pomegranate peel methanolic extract to extend semen collected from five native rams twice weekly for two months (n=80). Pooled (n=16) post-thaw semen characteristics were determined. Thawed seminal plasma of all supplemented and control groups were used to measure malondialdehyde (MDA), nitric oxide (NO), glutathione peroxidase (GPx), superoxide dismutase (SOD), ascorbic acid, zinc, copper, total cholesterol, low-density lipoproteins (LDL), lactate dehydrogenase (LDH), and alkaline phosphatase (ALP). Results: The supplementation of Tris-based semen extender with 0.48 mg/mL semen extender resulted in the highest post-thaw sperm total motility (P<0.001), sperm progressive motility (P<0.001), live sperm (P<0.001), sperm plasma membrane integrity (P<0.001), acrosome integrity (P<0.001), SOD (P<0.05), zinc (P<0.001), total cholesterol (P<0.001), and LDL (P<0.001) with the lowest percentage of abnormal sperm morphology (P<0.001), the lowest lipid peroxidation (MDA, P<0.01), ascorbic acid (P>0.05), and LDH (P>0.05). Conclusions: Pomegranate peel methanolic extract 0.48 mg/mL supplemented to Tris-based semen extender of rams is the best enrichment in preserving the sperm post-thaw characteristics via improving biochemical profiles and antioxidant capacity.